Retrospective cohort study of the risk factors for secondary infertility following hysteroscopic metroplasty of the uterine septum in women with recurrent pregnancy loss. (29th November 2017) - Ono, Shuichi; Yonezawa, Mirei; Watanabe, Kenichiro; Abe, Takashi; Mine, Katsuya; Kuwabara, Yoshimitsu; Akira, Shigeo; Takeshita, Toshiyuki
Abstract: Purpose: A hysteroscopic metroplasty was performed for women with recurrent pregnancy loss owing to a uterine septum, following which some women became infertile. The aim of this study was to elucidate the risk factors of secondary infertility 1 year after hysteroscopic metroplasty for a uterine septum. Methods: A retrospective, single‐center, cohort study included women with a history of at least two miscarriages that had been attributed to a uterine septum who underwent a hysteroscopic metroplasty. The patients' background data were compared between the patients who conceived and those who remained infertile at 1 year postoperatively. The data were analyzed by using the Mann–Whitney U‐test and multivariate analyses. Results: The postoperative live birth rate was 83.9% (n = 26), with persistent infertility in five women at 1 year. When comparing the pregnancy group with the infertile group, the women in the postoperative infertility group were significantly older than those in the postoperative pregnancy group. The multivariate analysis showed that age was an independent risk factor for persistent infertility. Conclusion: Age was identified as an independent risk factor for postoperative secondary infertility. Therefore, surgery as early as possible is recommended. Abstract : The risk factors for secondary infertility following hysteroscopic metroplasty of the uterine septum in women with recurrent pregnancy loss.